2015
DOI: 10.1140/epjst/e2015-02452-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of motility parameters from trajectory data

Abstract: Given a theoretical model for a self-propelled particle or micro-organism, how does one optimally determine the parameters of the model from experimental data in the form of a time-lapse recorded trajectory? For very long trajectories, one has very good statistics, and optimality may matter little. However, for biological micro-organisms, one may not control the duration of recordings, and then optimality can matter. This is especially the case if one is interested in individuality and hence cannot improve sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 55 publications
0
62
1
Order By: Relevance
“…In particular, a conceptually important question often raised within this context is if one can reliably extract information about the ensemble-averaged properties of random processes from single-trajectory data [46]. Considerable theoretical progress has been achieved, for instance, in finding the way to get the ensemble-averaged diffusion coefficient from a single Brownian trajectory, which task amounts to seeking properly defined functionals of the trajectory which possess an ergodic property (see, e.g., [43][44][45][46][48][49][50][51][52][53][54][55][56] for a general overview).One of such functionals used in single-trajectory analysis is the time-averaged mean squared displacement (MSD) (see, e.g., [39, 43-47])…”
mentioning
confidence: 99%
“…In particular, a conceptually important question often raised within this context is if one can reliably extract information about the ensemble-averaged properties of random processes from single-trajectory data [46]. Considerable theoretical progress has been achieved, for instance, in finding the way to get the ensemble-averaged diffusion coefficient from a single Brownian trajectory, which task amounts to seeking properly defined functionals of the trajectory which possess an ergodic property (see, e.g., [43][44][45][46][48][49][50][51][52][53][54][55][56] for a general overview).One of such functionals used in single-trajectory analysis is the time-averaged mean squared displacement (MSD) (see, e.g., [39, 43-47])…”
mentioning
confidence: 99%
“…To analyze the motility data from single molecules, initially, we assumed the simplest possible model: normal, free diffusion in the two dimensions of the cell membrane. Thus, we determined the diffusion coefficient for individual molecules along each coordinate axis using the near-optimal covariance-based estimator 26,27 (black points, Figure 3a Consequently, we could not reject the hypothesis that all molecules diffuse identically and that the observed variation simply is due to finite statistics ( Figure 3a,b). Comparison, of experimental and theoretical power-spectra for displacements 26,27 , however, demonstrated that this did not explain our data The MSDs deviated systematically from the straight line expected from normal, free diffusion of AQP3 in the plasma membrane ( Figure 3g).…”
Section: Spt-palm Reveals Confined Diffusion Of Aqp3-meos3 In the Plamentioning
confidence: 98%
“…The motion blur has even more effect on fast moving particles, as the particle observed position is the result of integration over longer areas. Including motion blur in the MSD leads to the following estimate for MSD [88] ⟨ρ n ⟩ = 2Dn∆t + 2(σ 2 − 2RD∆t).…”
Section: Comparison With Classical Single Particle Trajectories Analysismentioning
confidence: 99%